THE EFFECTIVENESS OF COMMUNICATION, INFORMATION, AND EDUCATION ON PARENTAL KNOWLEDGE OF PEDIATRIC RESPIRATORY INFECTION PATIENTS AT JOHAN PAHLAWAN HEALTH CENTER - Ayu Mardhana Lisa (PT. Radja Intercontinental Publishing, 2025)
Acute Upper Respiratory Infections (ARI) are among the leading infectious diseases contributing significantly to global morbidity and mortality, particularly among children under five years of age. Each year, an estimated four million deaths of children under five are attributed to ARI. Successful management of ARI can be improved when caregivers possess adequate knowledge about the disease and the correct use of medications. One approach to strengthening the role of caregivers is through the provision of Communication, Information, and Education (CIE). This study aimed to evaluate the effectiveness of CIE in improving the knowledge of caregivers of pediatric ARI patients at the Johan Pahlawan Community Health Center, West Aceh Regency. This study employed a quantitative approach with a pre-experimental design. The total sample consisted of 33 respondents, including parents or caregivers of pediatric ARI patients who visited the Johan Pahlawan Community Health Center. Data analysis was conducted using univariate analysis to describe the distribution of respondents’ knowledge levels and bivariate analysis using the Paired Sample t-test to assess the effectiveness of the CIE intervention. The results showed a p-value of 0.000 (p < 0.05), indicating a significant difference in knowledge levels before and after the CIE intervention. Therefore, it can be concluded that the provision of CIE is significantly effective in improving the knowledge of caregivers of pediatric ARI patients at the Johan Pahlawan Community Health Center, West Aceh Regency. Consequently, CIE should be implemented regularly and continuously as part of health promotion efforts to prevent and reduce the incidence of ARI among children.